2001
DOI: 10.1103/physrevb.64.094426
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic phase transition in disordered Fe-Ni alloys studied by means of small-angle neutron scattering and three-dimensional analysis of the neutron depolarization

Abstract: The magnetic phase transition in iron-nickel fcc alloys Fe 70 Ni 30 doped by carbon ͑0.7% at.͒ is investigated using the three-dimensional analysis of the neutron depolarization ͑ND͒ and small-angle neutron scattering ͑SANS͒. The coexistence and the growth of two different scale magnetic correlations are observed in a paramagnetic phase as temperature closes to T C . The usual critical fluctuations of a Lorentzian shape with size R c Ͻ200 Å are found by the analysis of SANS intensity I(q). The ND analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…4,5,8,9 As shown below, this assumption is confirmed by experimental data. Let us consider the presence of T C variations with a Gaussian distribution:…”
Section: A the Conceptsupporting
confidence: 74%
See 2 more Smart Citations
“…4,5,8,9 As shown below, this assumption is confirmed by experimental data. Let us consider the presence of T C variations with a Gaussian distribution:…”
Section: A the Conceptsupporting
confidence: 74%
“…In previous works 8, 9 we concluded from neutron depolarization ͑ND͒ and small-angle neutron-scattering ͑SANS͒ measurements that two different length scales for the magnetic correlations coexist in invar FeNi alloys around the mean critical temperature ͗T C ͘. Using SANS it was shown that the smaller length scale is attributed to the critical fluctuations and that their shape is well described by a Lorentzian in reciprocal space.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…which convolutes a scaling law for 3D Ising-like systems with a Gaussian distribution of local critical temperatures, T c s. 37 The dependence of T c with the applied magnetic field was neglected for simplicity and the critical exponent ␤ was taken as 0.33. 38 The experimental data were fairly well modeled using a mean critical temperature, ͗T c ͘, of 21.2 K ͑16.7 K͒ and a spread, ⌬T c , of 2.7 K ͑2.2 K͒ for the photoexcited ͑quenched͒ phase.…”
Section: Discussionmentioning
confidence: 99%
“…LOR is discovered in the magnetic phase transition in disordered systems. [4][5][6] The experiments on the superfluid transition of 4 He in porous media also revealed the localized Bose condensation above the global superfluid transition temperature. 7,8 In order to explain recent scanning tunnel microscope STM experiments, an inhomogeneous gapped superconductor with superconducting islands and metallic regions is proposed.…”
Section: Introductionmentioning
confidence: 94%